(untitled) (Contemporary Journal of Social Science Review, 2025)
This study uses a mixed-methodology to evaluate Karachi’s interbank offered rate (KIBOR), a financial phenomenon. The research objective is to determine the direct and indirect effects of KIBOR on borrowing and investment preferences, financial activities, and an economy by using quantitative analysis to apply statistics to numerical data from economics journals, financial statements, and online databases and qualitative analysis to interview key stakeholders and policymakers. Financiers, business companies, and those affected by KIBOR and monetary policies are prioritised in the sampling technique, boosting confidence in the study method. Data is collected from SBP annual reports, organisation financial year statements, officials, and stakeholders in semi structured and unstructured interviews. Quantitative analysis uses data patterns and tendencies to detect this, while simulation models show the sector’s performance with altering KIRB. The comprehensive strategy shows how KIBOR affects interest rates, credit availability, investment demand, and macroeconomic performance in Pakistan.